2019
DOI: 10.3390/biom9120839
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl Isothiocyanate Induces Apoptosis via Reactive Oxygen Species-Initiated Mitochondrial Dysfunction and DR4 and DR5 Death Receptor Activation in Gastric Adenocarcinoma Cells

Abstract: Benzyl isothiocyanate (BITC) is known to inhibit the metastasis of gastric cancer cells but further studies are needed to confirm its chemotherapeutic potential against gastric cancer. In this study, we observed cell shrinkage and morphological changes in one of the gastric adenocarcinoma cell lines, the AGS cells, after BITC treatment. We performed 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay, a cell viability assay, and found that BITC decreased AGS cell viability. Reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Apoptosis induction is considered an essential mechanism of antitumor therapeutics ( Stepczynska et al, 2001 ). Previous studies have revealed that anticancer agents impart anti-proliferative effects using two distinct apoptosis pathways that involve mitochondria or death receptors ( Kuo et al, 2018 ; Han et al, 2019 ). Specifically, the mitochondria-associated pathway is a classic intrinsic pathway that is caused by ROS overproduction, which in turn results in the depletion of △φin ( Shi et al, 2014 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induction is considered an essential mechanism of antitumor therapeutics ( Stepczynska et al, 2001 ). Previous studies have revealed that anticancer agents impart anti-proliferative effects using two distinct apoptosis pathways that involve mitochondria or death receptors ( Kuo et al, 2018 ; Han et al, 2019 ). Specifically, the mitochondria-associated pathway is a classic intrinsic pathway that is caused by ROS overproduction, which in turn results in the depletion of △φin ( Shi et al, 2014 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase 9, the initiator caspase in the mitochondria-dependent apoptosis pathway, activates the downstream effector Caspase 3, and active Caspase 3 impairs DNA repair through the cleavage of poly ADP-ribose polymerase (PARP). Excess ROS upregulate autophagy to remove proteins and organelles with oxidative damage in the cytoplasm [18][19][20][21]. LC3-phosphatidylethanolamine conjugate (LC3-II), a marker for autophagy, is involved in the formation of autophagosome membranes, and autophagosomes might fuse with lysosomes to degrade damaged cytosolic components [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This highlights that BITC is a good natural product for inhibiting S. typhimurium. Moreover, it has been proven by a large number of experimental studies that the antibacterial effect of BITC against foodborne pathogens is of great significance for food safety and clinical research [12,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Benzyl isothiocyanate (BITC) which is extensively found in senvy, pilu oil, cruciferous plants and papaya seeds [11], has been shown to exert potential health benefits to humans. According to the recent studies, BITC shows excellent therapeutic effects on cancer by reversing or blocking the proliferation of DNA-damaged precancerous cells [12][13][14]. In addition, BITC antibacterial mechanisms in foodborne bacteria have been widely studied.…”
Section: Introductionmentioning
confidence: 99%